Quilombola Community of Sítio Arruda: political, identity and territorial organization (Research, Society and Development, 2021)
This article characterizes the socio-anthropological point of view of the Quilombola Community of Sítio Arruda. For this, a bibliographical review is carried out, seeking to identify the primary elements of the community social organization, from a historical perspective. It is also intended to show the contemporary social life of the community, compromising potential and challenges faced. The traditional quilombola occupation of Sítio Arruda involves the migration of 3 (three) families from a place known as Sítio Coqueiro, which occurred in 1983. of historical and anthropological nature (Marques, 2010; Alves, 2018). The community's contemporary social life is characterized by its political organization, identity, cultural and religious manifestations. São dealt with the relations of two inhabitants as their own territory, highlighting the traditional knowledge linked to the sustainable management of two natural resources. Finally, gender relations are addressed, mainly highlighting the non-local female protagonism, based on the research by Felipe (2018) highlighting the central role that women have occupied both in the political processes of identity strengthening and in identity projects. community and we are cared for like a land.